Varying the regiochemistry of a [2 + 2] cycloaddition reaction within isostructural hydrogen bonded cocrystals containing 4-stilbazole. Issue 28 (13th June 2018) - Grobelny, Anna L.; Rath, Nigam P.; Groeneman, Ryan H.
Abstract : Cocrystallization of 4-stilbazole with 4, 6-diX resorcinol (X = Cl or Br) yields a pair of similar photoreactive solids that leads to different photoproducts. Abstract : Cocrystallization of 4-stilbazole with 4, 6-diX resorcinol (X = Cl or Br) yields a pair of photoreactive isostructural solids. Small variations in the spatial arrangement within each cocrystal leads to either the head-to-head (hh) or the unexpected head-to-tail (ht) photoproduct after undergoing a solid-state [2 + 2] cycloaddition reaction.